PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA PAPAN PINTAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD INPRES MALENGKERI II - Eva Kurniati; Andi Husniati, Kristiawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the STAD type cooperative learning model assisted by smart board media on students' mathematics learning outcomes. This type of research is a Pre-experimental study. With the research design is One Group Pretest-Posttest Design. The population of this study were all fourth-grade students of SD Inpres Malengkeri II, which consisted of two classes, namely class IV A and IV B. While the sample used in this study was random sampling. Random sampling is a random sampling technique, where each member of the population has an equal opportunity to be selected. The research instruments used were pretest-posttest test sheets, and observation sheets. The data analysis techniques used were descriptive statistical data analysis techniques and inferential data analysis. Based on the data obtained, it is known that the average learning outcomes before the treatment was given (pretest) was 35.28. While the learning outcomes after the treatment was given (posttest) was 80.88. These results indicate that the STAD type cooperative model assisted by smart board media has an effect on students' mathematics learning outcomes. Then the average increase in students' learning outcomes (N-Gain) was 0.71 with a high classification. The results of this study indicate that the Paired Sample T-Test results have a significance value (2-tailed) of <0.001. This significance value is much smaller than the 0.05 level of significance, so H_0 is rejected and H_1 is accepted. Therefore, H₀ is rejected and H₁ is accepted, indicating a significant difference in learning outcomes before and after the treatment. Based on these results, it can be concluded that the implementation of a cooperative learning model assisted by smartboard media has an impact on improving students' mathematics learning outcomes.